The Spanish Language and Military Education in Brazil (1905-1920) / A Língua Espanhola e a Educação Militar no Brasil (1905-1920) / La Lengua Española y la Educación Militar en Brasil (1905-1920) - Anselmo Guimarães; Josefa Eliana Souza (Universidade Federal de Uberlândia, 2018)
Este estudo é o resultado da investigação do processo de institucionalização do ensino de espanhol na educação militar brasileira, de 1905 a 1920, buscando delinear as finalidades políticas e culturais. O objetivo foi investigar as justificativas para a entrada do espanhol no ensino militar, no período de 1905, quando o idioma foi inserido oficialmente no currículo militar, mediante Decreto nº 5.698 e, finalizou em 1920, após reformularem os regulamentos militares e o ensino de espanhol deixar de ser oferecido no âmbito militar. Para tanto, foram utilizados a legislação educacional e textos jornalísticos, bem como pressupostos teóricos da história das disciplinas escolares. Palavras-chave: Educação Militar; História do Ensino de Espanhol; História das Disciplinas Escolares. Abstract This study is the result of the investigation of the process of institutionalization of the Spanish language teaching at the Brazilian military education, from 1905 to 1920, aiming at outlining political and cultural purposes. The goal has been to investigate the justifications for the insertion of the Spanish language in the Brazilian military education, starting in 1905, when the language has been officially inserted in the military curriculum under Decree No. 5.698 and ending in 1920, after the redesign of the military regulations and the fact that the Spanish language teaching has no longer been offered in the military scope. For this purpose, educational legislation and journalistic texts have been used, as well as theoretical assumptions of the history of school subjects. Keywords: Military Education; The History of the Spanish Language Teaching; The History of School Subjects. Resumen Este estudio es el resultado de la investigación del proceso de institucionalización de la enseñanza de español en la educación militar brasileña, de 1905 a 1920, buscando delinear las finalidades políticas y culturales. El objetivo fue investigar las razones de la entrada del español en la enseñanza militar, en el período de 1905, cuando el idioma fue introducido oficialmente en el plan de estudios militares por el Decreto nº 5.698 y terminado en 1920, después de reformularen los reglamentos militares y la enseñanza del español salió del ámbito militar. Por lo tanto, hemos utilizado la legislación educativa y textos periodísticos, así como supuestos teóricos de la historia de las disciplinas escolares. Palabras clave: Educación Militar; Historia de la Enseñanza del Español; Historia de las Disciplinas Escolares.